The VEGFA gene and anterior cruciate ligament rupture risk in the Caucasian population - Ewelina Lulińska-Kuklik; Katarzyna Leźnicka; Kinga Humińska-Lisowska; Waldemar Moska; Monika Michałowska-Sawczyn; Zbigniew Ossowski; Ewelina Maculewicz; Paweł Cięszczyk; Mariusz Kaczmarczyk; Wojciech Ratkowski; Krzysztof Ficek; Piotr Zmijewski; et al. (Termedia Publishing House, 2018)
The aim of the present study was to analyse VEGFA rs699947, rs1570360, and rs2010963 polymorphisms with susceptibility to anterior cruciate ligament rupture (ACLR) in a Polish population. The study included 412 physically active Caucasian participants. The study group consisted of 222 individuals with surgically diagnosed primary ACLR qualified for ligament reconstruction (ACLR group). The control group consisted of 190 apparently healthy participants without any history of ACLR (CON group). Three polymorphisms within the VEGFA (rs699947, rs1570360, and rs2010963) gene were chosen for investigation due to their significance in the angiogenesis signalling pathway and previous associations with risk of ACLRs. Both single-locus and haplotype-based analyses were conducted. No significant differences in the allele and genotype frequency distributions were noted for the rs699947 and rs1570360 polymorphisms. In contrast, rs2010963 was associated with risk of ACLR in the codominant (p=0.047) and recessive model (p=0.017). In the latter, the CC genotype was overrepresented among individuals with ACL rupture (23.4% vs 14.2%, OR=1.85 [1.11-3.08]). Two VEGFA haplotypes were associated with ACLR under the additive (global score=11.39, p=0.022) and dominant model (global score=11.61, p=0.020). The [C;G;G] haplotype was underrepresented in the ACLR group (52.2% vs. 60.3%), whereas the [C;G;C] haplotype was overrepresented (2.9% vs 0.5%). The results obtained suggest a potential correlation between the VEGFA rs2010963 polymorphism and ACLR risk, suggesting that harbouring this specific C allele may be an unfavourable risk factor for a knee injury in Caucasian participants from Poland.